Revolutionizing Sports: The Role of Wearable Technology and AI in Training and Performance Analysis - Stanisław Dudek; Weronika Koziak; Michalina Makieła; Aleksandra Bętkowska; Agata Kornacka; Wojciech Dudek; Kamila Szostak; Rafał Tomaka; Anna Byra (Quality in Sport)
The integration of wearable technology and artificial intelligence (AI) has transformed modern sports science by enhancing athlete monitoring, performance optimization, and injury prevention. Wearable sensors, including fitness trackers, GPS-based devices, and biomechanical motion trackers, provide real-time physiological and biomechanical data, enabling personalized training programs and workload management. AI-driven analytics, utilizing machine learning, deep learning, and computer vision, enhance performance assessment, injury prediction, and rehabilitation strategies by processing vast datasets to detect fatigue patterns, optimize recovery schedules, and refine tactical decision-making.